Location of Repository

∀u, t 0 ≤ u ≤ t g(t) − g(u) ≤ − (λg(s) + C)ds (1) Then

By Quang-cuong Pham


We prove a variation of Gronwall’s lemma. The formulation and proof of the classical Gronwall’s lemma can be found in [1]. We prove here a variation of this lemma, which we were not able to find in the literature. Lemma 1 Let g: [0, ∞[ → R be a continuous function, λ> 0 and C ≥ 0. Assume that ∫

Year: 2009
OAI identifier: oai:CiteSeerX.psu:
Provided by: CiteSeerX
Download PDF:
Sorry, we are unable to provide the full text but you may find it at the following location(s):
  • http://citeseerx.ist.psu.edu/v... (external link)
  • http://arxiv.org/pdf/0704.0922... (external link)
  • Suggested articles

    To submit an update or takedown request for this paper, please submit an Update/Correction/Removal Request.